The total cost of trading Belgian shares: Brussels versus London - Degryse, Hans (Journal of Banking & Finance, 1999)
Since 1990, London’s SEAQ International (SEAQ-I) has attracted considerable trading volume in Belgian equities. This paper investigates competition between the Brussels CATS market and London’s SEAQ-I. Toward this end, we gathered extensive limit order book data as well as transactions and quotation information. With regard to liquidity (indirect costs), measured by the quoted and effective bid–ask spread, the paper concludes that CATS outperforms SEAQ International for both measures. The effective spread is of course substantially smaller than the quoted spread, with the CATS effective spread showing a U-shaped form. This paper, unique in employing an extensive data set that includes all hidden orders and the whole limit order book, produces results in line with the different market microstructure models. Total trading costs on CATS are lower (higher) for small (large) trade sizes.